Research on Integrated Crop-Livestock Systems in Brazil - de Moraes, Anibal; Carvalho, Paulo César; Lustosa, Sebastião; Lang, Claudete; Deiss, Leonardo (Revista Ciência Agronômica, 2014)
Integrated crop-livestock systems (ICLS) are designed to exploit synergisms and emergent properties resulting from interactions between different soil-plant-animal-atmosphere compartments that integrate themselves at different spatial-temporal scales. In this review, a panorama of the evolution of studies based on ICLS is presented. Specific keywords were used as search terms to construct a database of 450 articles from 93 national and international journals published up to and including 2013. These articles were classified according to the region of origin within Brazil (subtropical or tropical) and categorized regarding the studied components: soil, plant, animal and ‘others’. Within these components, groups of variables that could characterize the different thematic lines were listed. The number of publications worldwide has been increasing, and Brazil is one of the main suppliers of scientific work within this area. Although the number of scientific studies seeking better understanding of ICLS may have increased in Brazil, further studies with a systematic view and with larger temporal and spatial scales are still required to help identify interactions between diverse biotic and abiotic factors that define new properties that emerge from these systems.